Mobile phone addiction and academic burnout: the mediating role of technology conflict and the protective role of mindfulness - Yang, Guang-Hui; Cao, Xiao-Xuan; Fu, Yan-Yan; Wang, Ning-Dan; Lian, Shuai-Lei (Frontiers in Psychiatry, 2024)
With the rapid development of Internet technology, more and more college students are facing the threat of mobile phone addiction. However, the relationship and underlying mechanism between mobile phone addiction and academic burnout haven't been explored in depth. This study proves the mediating role of technology conflict and the moderating role of mindfulness in the relation between mobile phone addiction and academic burnout. 752 college students were recruited to complete the questionnaire of mobile phone addiction, technology conflict, mindfulness and academic burnout. Results showed that mobile phone addiction was significantly and positively associated with academic burnout, and this relationship could be mediated by technology conflict.Besides, the direct effect of mobile phone addiction on academic burnout and the indirect effect of technology conflict in this link were moderated by mindfulness. Both these two effects are stronger for college students with lower level of mindfulness. Our findings enrich our understanding of how and when mobile phone addiction was related to academic burnout.Educational professionals and parents should take timely measure to the academic burnout of college students suffering from mobile phone addiction, particularly for those with lower level of mindfulness.